Diversity and distribution of the free-living freshwater Cyclopoida (Copepoda: Crustacea) in the Neotropics - Silva,WM. (2008)
Cyclopoida species from the Neotropics are listed and their distributions are commented. The results showed 148 species in the Neotropics, where 83 species were recorded in the northern region (above upon Equator) and 110 species in the southern region (below the Equator). Species richness and endemism are related more to the number of specialists than to environmental complexity. New researcher should be made on to the Copepod taxonomy and the and new skills utilized to solve the main questions on the true distributions and Cyclopoida diversity patterns in the Neotropics.